Laureano Segovia: Literature of oral tradition and political resistance in Nolhamelh culture - Rivera Giardinaro, Pamela Rosa Amelia (2021)
The Nolhamelh (Wichí) indigenous culture, in the territory belonging to the South American Gran Chaco region, has a collective memory that, throughout the 20th century, has been integrating written expression in coexistence with orality. Here I focus on the Olhamel Otichunhayaj books. Our memory (1998) and Olhamel ta ohapehen wichi. We, the Wichí (2011) by the writer Laureano Segovia to give an account of a literature of oral tradition (Espino Relucé, 2010) that includes the testimonial record prepared by the author together with his own literary word. Likewise, this production continues the elaboration of the collective identity nolhamelh thematizing the conflictive relationship with the white or Creole man, the link with the land / nature and the importance of the original language as current forms of cultural resistance (Calveiro, 2018). Therefore, one can speak of one more expression within the framework of alternative literatures (Lienhard, 1992) in Latin America.